The Application of Supply Chain Risk Management Assessment in Smallscale Fisheries in Bangka Belitung, Indonesia Using Probabilistic Risk Analysis (PRA) Method - Ardiatika, Yugo; Mahjoub, Mohamed-Badrane; Novieningtyas, Annisaa (Fakultas Ekonomi dan Bisnis, Telkom University., 2023)
Indonesia’s small-scale fisheries contributed as the second large fishing country which create an economy of scale throughout the food security. However, fish capturing from the indigenous livelihood weighed an inefficiency on the production volume due to limited resources and knowledge. The research aims to benefit by applying supply chain risk management on fishery products in Bangka Belitung, Indonesia across its regencies with product-hub placement. The objective is to identify the local risk distributions and most vital causes to cumulative losses for specific fish commodities. The research would specify the least to most common risk occurred. The research is a triangulation method consisting of probabilistic risk analysis, interviews, and direct observations. The result showed there is a significant level of risk outspread around each municipality in Bangka Belitung, showing from the capture, sampling, and fishery businesses production data. The lead time in days and price per unit became the two main factors as it validates the risk occurrence. The government strategy was limited on the high number of volume and potentials, a case would be shrimps. Indeed, there is an indication that high risks are occurring in most small lead time fishery businesses across Bangka Belitung with mackerel fish as the main spoilage, followed by crab, and yellow-tail scads. The findings showed there is an average of 35,00% risk inside 30,36% fishery businesses in Bangka Belitung and the risk impact per business capture ranged between 0,33 to 0,77 probability. The total risk for price reached 94.78% of the total fish commodities. Keywords—Probabilistic Risk Analysis; Product-Hub; Risk Management; Small-Scale Fisheries; Supply Chain